2017
DOI: 10.1016/j.ajic.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination among workers—21 U.S. states, 2013

Abstract: Background Influenza illnesses can result in missed days at work and societal costs, but influenza vaccination can reduce the risk of disease. Knowledge of vaccination coverage by industry and occupation can help guide prevention efforts and be useful during influenza pandemic planning. Methods Data from 21 states using the 2013 Behavioral Risk Factor Surveillance System (BRFSS) industry/occupation module were analyzed. Influenza vaccination coverage was reported by select industry and occupation groups, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Differences in vaccination acceptance were found among different occupations, which may be attributed to differences in knowledge of and attitude to prevention precautions among occupations [ 42 ]. The clerical, sales and service workers had a lower willingness to accept the COVID-19 vaccine than the others, which is similar to findings from the US that influenza vaccination coverage was lower in sales and service workers than most occupations [ 43 ]. They were also more likely to believe that the vaccination is unnecessary, which might result from a lower health literacy or the belief that the threats of the pandemic were exaggerated [ 16 ].…”
Section: Discussionsupporting
confidence: 79%
“…Differences in vaccination acceptance were found among different occupations, which may be attributed to differences in knowledge of and attitude to prevention precautions among occupations [ 42 ]. The clerical, sales and service workers had a lower willingness to accept the COVID-19 vaccine than the others, which is similar to findings from the US that influenza vaccination coverage was lower in sales and service workers than most occupations [ 43 ]. They were also more likely to believe that the vaccination is unnecessary, which might result from a lower health literacy or the belief that the threats of the pandemic were exaggerated [ 16 ].…”
Section: Discussionsupporting
confidence: 79%
“…NIOCCS has been previously reviewed by Schmitz et al and Weiss et al to show feasibility of use, however, additional testing in various datasets is necessary to demonstrate performance capabilities. This program has recently been used to categorize occupational information in Behavioral Risk Factor Surveillance System (BRFSS) data . Details of SOCcer are described by Russ along with preliminary testing.…”
Section: Introductionmentioning
confidence: 99%
“…This program has recently been used to categorize occupational information in Behavioral Risk Factor Surveillance System (BRFSS) data. 14,15 Details of SOCcer are described by Russ 16 along with preliminary testing. However, to our knowledge, SOCcer has not been formally tested by researchers unaffiliated with the development team.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that among the risk factors associated with AFV are age12 14 23 (in years), gender12 14 23 (female, male), race/ethnicity12 17 18 (non-Hispanic white, non-Hispanic black, non-Hispanic other, Hispanic), marital status12 32 (married or a member of an unmarried couple; separated, divorced or widowed; never married), education level12 17 23 (less than high school graduate; high school graduate; some college or technical school; college graduate or more), employment status14 15 17 22 (employed for wages or self-employed; home maker or student or retired; out of work; unable to work) and income14 23 28 (<US$15 000; US$15 000 to <US$25 000; US$25 000 to <US$35 000; US$35 000 to <US$50 000; US$50 000 or more). Therefore, these variables were included in the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Prior research has explored possible causes of low vaccination rates, including personal attitudes towards vaccinations,14 17 18 lack of awareness and acceptance of the benefits of vaccination,14 19 geographical constraints,12 20 21 employment type,22 and ethnic/racial disparities 14 18. Another barrier affecting AFV rates in the USA is whether an individual has health insurance coverage 23…”
Section: Introductionmentioning
confidence: 99%